Het lot van psychiatrische patiënten in Nederland tijdens de Tweede Wereldoorlog: Een reviewartikel over de studie van Eveline Buchheim en Ralf Futselaar: Uit zorg verdreven. Het Nederlandse Krankzinnigenwezen tijdens de Tweede Wereldoorlog (Boom 2023). - aan de Stegge, Cecile; Beaufort, Lucie; Schuurmans, Rense; Stienen, John (BMGN - Low Countries Historical Review, 2025)
In the study Uit zorg verdreven. Het Nederlandse Krankzinnigenwezen tijdens de Tweede Wereldoorlog (Expelled from Care: Dutch Asylums for the Mentally Ill During the Second World War), Eveline Buchheim and Ralf Futselaar analyse the mortality rates among patients in Dutch psychiatric institutions during the German Occupation (1940-1945). Using patients’ age and the duration of their stay in 4 selected facilities out of a total of 30 institutions, they attribute the dramatic increase in patient mortality during the war to changing admission policies that favoured the old and infirm. However, we found no evidence for this interpretation in the archives of the institutions that we researched ourselves. From our analysis, we conclude that several external factors are more plausibly linked to the increase in mortality. Especially the forced mass evacuations of several institutions imposed by the occupying forces had a strong impact, leading to an overall worsening of living conditions in the institutions, which resulted in overcrowding, poor nutrition and greatly increased tuberculosis mortality.